Synthesis and characterization of chitosan nanoparticles decorated with folate and loaded with dasatinib for targeting folate receptors in cancer cells - Smita Tukaram Kumbhar; Ravikant Yashwantrao Patil; Manish Sudesh Bhatia; Prafulla Balkrushna Choudhari; Vinod Limbraj Gaikwad (Elsevier, 2022)
ABSTRACT: Background: This study produced these Folate-Chitosan (FA-CS) conjugates by coupling a reaction with FA with CS, which resulted in better performance than previously attained due to the preservation of CS's basic chemical properties as well as the integration of the folate targeting receptor. Methods: The FA-CS conjugates were synthesised using tripolyphosphate (TPP), which is based on the chemical conjugation of the amino group of CS with the carboxylic group of FA and was validated using FTIR and 1H NMR spectroscopy, respectively. Results: The FA-CS-NPs were shown to exhibit a unique core-shell structure under transmission electron microscopy; the encapsulation efficiency EE (percentage) and loading efficiency LE (percentage) of Dasatinib in FA-CS-DS-NPs were 50.7 ± 0.27% and 12.8 ± 0.21%, respectively. The FA-CS-DS-NPs exhibited a homogenous particle distribution of 103.17 ± 5.20 nm (PDI 0.081, zeta potential 20.2 ± 5.9 mV). As the pH of the dissolving solution lowers, the rate of DS release from the NPs increases, indicating that DS release from FA-CS-DS-NPs may be higher in a low pH environment than in a high pH environment. The MTT assay was used to examine the cell viability profile, which indicated that FA-CS-NPs did not induce significant cytotoxicity. In the cellular uptake study, for example, the intracellular concentration of DS in MCF-7 cells after exposure to FA-CS-DS-NPs was considerably higher than the concentration of DS in cells exposed to DS alone. Conclusion: As a result, FA-CS-DS-NPs show promise as a cancer therapeutic drug delivery mechanism.